2022
DOI: 10.3389/fmicb.2022.843041
|View full text |Cite
|
Sign up to set email alerts
|

The Biocontrol Functions of Bacillus velezensis Strain Bv-25 Against Meloidogyne incognita

Abstract: Meloidogyne incognita is obligate parasitic nematode with a wide variety of hosts that causes huge economic losses every year. In an effort to identify novel bacterial biocontrols against M. incognita, the nematicidal activity of Bacillus velezensis strain Bv-25 obtained from cucumber rhizosphere soil was measured. Strain Bv-25 could inhibit the egg hatching of M. incognita and had strong nematicidal activity, with the mortality rate of second-stage M. incognita juveniles (J2s) at 100% within 12 h of exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 50 publications
2
25
1
3
Order By: Relevance
“…B. velezensis is a widely reported plant growth-promoting rhizobacteria (PGPR) and a beneficial endophyte. Inoculation with B. velezensis can promote the growth of plants [ 18 ] and prevent many plant diseases [ 19 , 20 , 21 , 22 ]. Furthermore, B. velezensis can form stable endospores that help them survive in the preparation of bacterial bioinoculants [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…B. velezensis is a widely reported plant growth-promoting rhizobacteria (PGPR) and a beneficial endophyte. Inoculation with B. velezensis can promote the growth of plants [ 18 ] and prevent many plant diseases [ 19 , 20 , 21 , 22 ]. Furthermore, B. velezensis can form stable endospores that help them survive in the preparation of bacterial bioinoculants [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, not all microbial BCAs have suppressive effects on nematodes. Many bacteria and fungi (some of which are endophytes), including arbuscular mycorrhizal fungi (AMF), have plant-promoting effects instead and can induce plant defense mechanisms against PPNs, namely, by managing phytohormone levels, inducing signal substrate production, regulating gene expression, and enhancing protein production, and they have been extensively used as plant health promoters and BCAs against harmful nematodes [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Bacterial mechanisms to antagonize PPNs may include the production of antibiotics, endospores, hydrolytic enzymes, volatile organic compounds (VOCs), Cry proteins (pore-forming toxins), and Trojan horses, which lure nematodes by emitting VOCs and secreting proteases or toxins upon entry into their host, ultimately killing the nematode [ 17 , 38 , 39 , 40 ] ( Figure 2 ).…”
Section: Microbes Against Plant-parasitic Nematodesmentioning
confidence: 99%
“…Indeed, salicylic acid (SA)- and jasmonic acid (JA)-related genes were primed at different times after nematode inoculation in tomato, but only the SA-related gene was upregulated at 7 days after nematode inoculation in cucumber [ 31 ]. Tian et al [ 32 ] assessed the nematicidal activity of B. velezensis Bv-25 against M. incognita and its overall effects on cucumber and found that this strain inhibited egg hatching and produced a 100% mortality rate of J2s within 12 h of exposure to Bv-25 fermentation broth in vitro. Furthermore, Bv-25 colonized cucumber roots, effectively reducing the infection rate of J2s by 98.6% [ 32 ].…”
Section: Microbes Against Plant-parasitic Nematodesmentioning
confidence: 99%
See 2 more Smart Citations